Relationship between cold pressor pain-sensitivity and sleep quality in opioid-dependent males on methadone treatment - Nasir, Mohamad; Zalina, Zahari; Chee Siong, Lee (2015)
Aim. Poor sleep quality due to pain has been reported among opioid-dependent male patients on methadone maintenance therapy (MMT) but objective pain data are lacking. This study aimed to investigate the rate of pain-sensitivity using cold pressor test (CPT) and the relationship between pain-sensitivity and sleep quality in this population. Methods. A total of 168 male participants were included into the study. Objective pain-tolerance was evaluated at 0 h and at 24 h after the first CPT. Malay version of the Pittsburgh Sleep Quality Index (PSQI) and the subjective opiate withdrawal scale (SOWS) questionnaires were administered to evaluate the quality of sleep and withdrawal symptoms, respectively. Results. The mean age of study participants was 37.22 (SD 6.20) years old. Mean daily methadone dose was 76.64 (SD 37.63) mg/day, mean global PSQI score was 5.47 (SD 2.74) and mean averaged SOWS score was 5.43 (SD 6.91). The averaged pain-tolerance time ranged from 7 to 300 s with a mean time of 32.16 (SE 2.72) s, slightly below the cut-off score of 37.53 s. More specifically, 78.6% (n = 132) of participants were identified as pain-sensitive (averaged pain-tolerance time ≤37.53 s), and 36 (21.4%) participants were pain-tolerant (averaged pain-tolerance time >37.53 s). The pain-sensitive group reported poorer sleep quality with mean (SD) PSQI of 5.78 (2.80) compared with the pain-tolerant group with mean (SD) PSQI of 4.31 (2.18) (p = 0.005). With analysis of covariance, pain-sensitive group was found to have higher global PSQI scores (adjusted mean 5.76, 95% CI 5.29; 6.22) than pain-tolerant participants (adjusted mean 4.42, 95% CI 3.52; 5.32) (p = 0.010). Conclusions. Majority of opioid-dependent male patients on methadone treatment are pain-sensitive with CPT. Poor sleep quality is associated with cold pressor pain-sensitivity. Pain and sleep complaints in this male population should not be overlooked.